Local Drug Delivery for Prevention of Hearing Loss - Rybak, Leonard P.; Dhukhwa, Asmita; Mukherjea, Debashree; Ramkumar, Vickram (Frontiers in Cellular Neuroscience, 2019)
Systemic delivery of therapeutics for targeting the cochlea to prevent or treat hearing loss is challenging. Systemic drugs have to cross the blood-labyrinth barrier (BLB). BLB can significantly prevent effective penetration of drugs in appropriate concentrations to protect against hearing loss caused by inflammation, ototoxic drugs, or acoustic trauma. This obstacle may be obviated by local administration of protective agents. This route can deliver higher concentration of drug compared to systemic application and preclude systemic side effects. Protective agents have been administered by intra-tympanic injection in numerous preclinical studies. Drugs such as steroids, etanercept, D and L-methionine, pifithrin-alpha, adenosine agonists, melatonin, kenpaullone (a cyclin-dependent kinase 2 (CDK2) inhibitor) have been reported to show efficacy against cisplatin ototoxicity in animal models. Several siRNAs have been shown to ameliorate cisplatin ototoxicity when administered by intra-tympanic injection. The application of corticosteroids and a number of other drugs with adjuvants appears to enhance efficacy. Administration of siRNAs to knock down AMPK kinase, liver kinase B1 (LKB1) or G9a in the cochlea have been found to ameliorate noise-induced hearing loss. The local administration of these compounds appears to be effective in protecting the cochlea against damage from cisplatin or noise trauma. Furthermore the intra-tympanic route yields maximum protection in the basal turn of the cochlea which is most vulnerable to cisplatin ototoxicity and noise trauma. There appears to be very little transfer of these agents to the systemic circulation. This would avoid potential side effects including interference with anti-tumor efficacy of cisplatin. Nanotechnology offers strategies to effectively deliver protective agents to the cochlea. This review summarizes the pharmacology of local drug delivery by intra-tympanic injection to prevent hearing loss caused by cisplatin and noise exposure in animals. Future refinements in local protective agents provide exciting prospects for amelioration of hearing loss resulting from cisplatin or noise exposure.